Early Nineteenth-Century Biblical Scholarship and the Production of The Book of Mormon - Townsend, Colby (Journal of the bible and its reception, 2025)
Scholars have long written about the development of biblical criticism and its reception in elite circles in the transatlantic world of the seventeenth through the nineteenth centuries. This has caused us to assume that non-elites were unaware of the developments in biblical studies. Anglophone readers of the Bible were increasingly accepting the work of biblical scholars and, as Paul Gutjahr has shown, came to view their copies of the Bible as fallible representations of what scripture would have been in its original. The example of one non-elite, Joseph Smith Jr., might help us to rethink our assumptions and reframe the questions we ask about the reception history of biblical criticism because he engaged with biblical scholarship in a creative way as he tried to restore the text of Isaiah 2-14, 29, and 48-54 in The Book of Mormon (1830). Smith likely used Adam Clarke’s commentary on the Bible as he dictated these lengthy chapters of Isaiah into the narrative framing of the book. While the source text is clearly the KJV there are several variants throughout that deviate from it, but they are in Clarke’s commentary. Smith did not slavishly copy Clarke but engaged critically with his notes and paratext, incorporating what he saw as useful so that he could revise and attempt to restore Isaiah.